2011
DOI: 10.1007/128_2011_124
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Atom Donors: Recent Developments

Abstract: This review highlights recent developments in the field of hydrogen atom transfer (HAT) reagents that circumvent the disadvantages of classical group 14 reagents, such as Bu₃SnH. Special emphasis is laid on the lowering of bond dissociation energies (BDEs) of molecules that could, as yet, not be used as HAT reagents and on the use of organometallic HAT reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 89 publications
0
39
0
Order By: Relevance
“…[4,15] To this end, Wilkinsons catalyst [Rh(PPh 3 ) 3 Cl] (36) [16] or Crabtrees catalyst [Ir(cod)PyPCy 3 ]PF 6 (37) [17] were employed together with Zn-1.B oth catalysts resulted in ar emarkable acceleration in the formation of 4 (Scheme 5). [4,15] To this end, Wilkinsons catalyst [Rh(PPh 3 ) 3 Cl] (36) [16] or Crabtrees catalyst [Ir(cod)PyPCy 3 ]PF 6 (37) [17] were employed together with Zn-1.B oth catalysts resulted in ar emarkable acceleration in the formation of 4 (Scheme 5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,15] To this end, Wilkinsons catalyst [Rh(PPh 3 ) 3 Cl] (36) [16] or Crabtrees catalyst [Ir(cod)PyPCy 3 ]PF 6 (37) [17] were employed together with Zn-1.B oth catalysts resulted in ar emarkable acceleration in the formation of 4 (Scheme 5). [4,15] To this end, Wilkinsons catalyst [Rh(PPh 3 ) 3 Cl] (36) [16] or Crabtrees catalyst [Ir(cod)PyPCy 3 ]PF 6 (37) [17] were employed together with Zn-1.B oth catalysts resulted in ar emarkable acceleration in the formation of 4 (Scheme 5).…”
Section: Methodsmentioning
confidence: 99%
“…[1] In chain reactions,HAT has usually been carried out with Bu 3 SnH, [1] (Me 3 Si) 3 SiH, [2] or NHC-Boranes as stoichiometric H-atom donors. [4,5] An attractive alternative for HATc atalysis that does not require the use of H 2 is lowering of the bond dissociation energy (BDE) of molecules with strong OÀH bonds,such as H 2 OorCH 3 OH, by coordination to low-valent metal reagents,s uch as titanocene(III) complexes. [4,5] An attractive alternative for HATc atalysis that does not require the use of H 2 is lowering of the bond dissociation energy (BDE) of molecules with strong OÀH bonds,such as H 2 OorCH 3 OH, by coordination to low-valent metal reagents,s uch as titanocene(III) complexes.…”
mentioning
confidence: 99%
“…29,375 Like those of Halpern, these early studies focused on reductions of activated alkenes such as polyaromatic compounds, styrenes, acrylates, 1,3-dienes and allenes with transition metal hydrides bearing strongly π-acidic ligands like :C≡O along with a phosphine or Cp/Cp * ligand. 375 However, addition across unactivated alkenes was not observed.…”
Section: Hydrogenation and Isomerizationmentioning
confidence: 99%
“…Thus, we do not discuss generation of carbon centered radicals from functionalities other than C=C bonds, such as epoxides, alcohols and carbonyls. 29 We do not discuss hydrides of second and third row transition metals, nor of group 13 and 14 metalloid-hydrides (i.e. [Si]-H, [Ge]-H, [Sn]-H, [Pb]-H), hydrogen atom transfer from C-H bonds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the difference in structure between DHI and DHICA, oxidative polymerization of DHICA to melanin mainly leads to limited conjugation, and therefore relatively little absorption above 400 nm, whereas DHI generates planar species that strongly absorb in the visible region From the results of free radical scavenging experiments, Panzella et al reported that DHICA has significantly better free radical scavenging properties and is a stronger hydrogen atom donor than DHI . This latter claim has been disputed by Gaensauer et al …”
Section: Melanin Biosynthesismentioning
confidence: 99%